Fabricación de bronce al manganeso uns c86500 según norma astm b584 para aplicaciones marinas - Palacios Cevallos, Víctor Rafael (2009)
This work is focused in the fabrication of UNS C86500 brass based on recicled materials; the process starts in the laboratory with small melts which are analysed by tha atomic abstortion method to know the chemical compositions and correct them progrssively untill we reach the results that are consistent with the ASTM B584 standard. Once we’ve reached the chemical composition, the rest of the tests (tension, metalography, hardness) for characterization of materials are performed. The resultsobtained were verified by the fabrication of a large scale ship propeller in the artisan workshop that has made this products with recycled brass materials for over fifty years. The experience served to change the production with little or no control on the procedure recommended herein and that has the garantee of the results consistent with the standard.